2001
DOI: 10.1176/appi.ps.52.7.903
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practices for Services to Families of People With Psychiatric Disabilities

Abstract: Family psychoeducation is an evidence-based practice that has been shown to reduce relapse rates and facilitate recovery of persons who have mental illness. A core set of characteristics of effective family psychoeducation programs has been developed, including the provision of emotional support, education, resources during periods of crisis, and problem-solving skills. Unfortunately, the use of family psychoeducation in routine practice has been limited. Barriers at the level of the consumer and his or her fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
274
0
19

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(305 citation statements)
references
References 58 publications
12
274
0
19
Order By: Relevance
“…Family psychoeducation has been shown to reduce relapse and the need for hospitalization in addition to improving the well-being of family members who participated (Dixon, et al, 2001). The Schizophrenia Patient Outcomes Research Team recommends that family members who have contact with a relative who is mentally ill be offered family psychosocial intervention addressing illness education, family support, crisis intervention, and skills training, lasting a minimum of nine months (Dixon, Goldman & Hirad, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Family psychoeducation has been shown to reduce relapse and the need for hospitalization in addition to improving the well-being of family members who participated (Dixon, et al, 2001). The Schizophrenia Patient Outcomes Research Team recommends that family members who have contact with a relative who is mentally ill be offered family psychosocial intervention addressing illness education, family support, crisis intervention, and skills training, lasting a minimum of nine months (Dixon, Goldman & Hirad, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…More often, consumers now expect caregivers to be capable of providing information about treatment options and engaging them in collaborative decision-making in treatment planning. This unique set of practitioner competencies is seldom addressed in education and training programs (Chinman et al, 1999;Dixon et al, 2001;Young, Forquer, Tran, Starzynski, & Shatkin, 2000).…”
Section: The Emerging Focus On Competency In Healthcarementioning
confidence: 99%
“…Family psycho-education and behavioural management interventions for people with schizophrenia are the most frequently used approaches in Western countries (Dixon et al, 2001, Sellwood et al, 2001. Three recent reviews of more than 15 controlled trials concluded that family psycho-education programmes have demonstrated significant positive effects in improving knowledge about mental illness and drug compliance and reducing relapse rates (Pharoah et al, 2010, Pitschel-Walz et al, 2004, Rummel-Kluge and Kissing, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is increasing research evidence (e.g., Dixon et al, 2001, Lehman et al, 2004 indicating that the common therapeutic components in the approaches to family intervention, including the sharing of information, psychological support, and practical assistance between peer participants, are associated with greater improvements in the ability of family members to cope with the stress and demands of taking care of a relative with schizophrenia and other severe mental illnesses (Chien and Norman, 2009). Therefore, there is a need to investigate whether any alternative models of family intervention can be effective in improving the psychosocial functioning and well-being of both families and patients.…”
Section: Introductionmentioning
confidence: 99%